1998
DOI: 10.1142/s0218625x98001407
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectron-Diffraction Studies of Nb(001)

Abstract: Photoelectron-diffraction studies of Nb(001) have been performed to determine the first-interlayer contraction using Mg Kα radiation (hν = 1253.6 eV) as an excitation source. Photoemission intensities of the 3d 5/2 core level were measured as a function of the polar angle along several azimuths on the single-crystal surface. The 202.3-eV (205.0-eV) binding energy for the 3d 5/2 (3d 3/2 ) core level was well resolved in the photoemission spectra, where the peak intensity could be easily evaluated by curve-fitti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
4
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 22 publications
3
4
0
Order By: Relevance
“…12). Similar angular distributions for a Nb(0 0 1) substrate were obtained experimentally and theoretically in fully dynamic multiple-scattering calculation of the Nb-3d lines [55]. The dynamic calculations showed that intensity maxima appear along close-packed crystalline axes.…”
Section: Subsurface Pdsupporting
confidence: 78%
“…12). Similar angular distributions for a Nb(0 0 1) substrate were obtained experimentally and theoretically in fully dynamic multiple-scattering calculation of the Nb-3d lines [55]. The dynamic calculations showed that intensity maxima appear along close-packed crystalline axes.…”
Section: Subsurface Pdsupporting
confidence: 78%
“…As shown in Table II, a large inward relaxation of the top layer is noted. The converged Nb(100) surface layer contraction Ád 12 (À11:7%) is consistent with TB data using 20 atomic layers 46) and photoelectron diffraction (PP) studies, 50) while the results differ from other TB quenched molecular dynamics (TB-QMD) (À6:3%) and FP-LMTO (À9:3%) in which 6 or 7 layer slab and 20 k-point were used. For the inner layer, small expansion approximately +0.3 and +2.1% for the second and third atomic layer are found, respectively, which nevertheless is less significant than that of the surface layer.…”
Section: A Bulk Clean Surfaces and A Free No Moleculesupporting
confidence: 76%
“…Table VII lists the percent change in spacing between the first and second surface layers relative to the spacing in the bulk. We compare our EAM results to our DFT calculations, experimental data, 63 and published EAM, 8 F-S, 62 and MEAM ͑Ref. 11͒ results.…”
Section: Surface Propertiesmentioning
confidence: 94%
“…The number of layers in our slabs are in parentheses. Experimental data from Lo et al63 .c EAM results of Guellil and Adams 8 . d F-S results of Ackland and Finnis 62 .…”
mentioning
confidence: 99%